Associations between benign paroxysmal positional vertigo and seven mental disorders: a two-sample Mendelian randomization study - Liu, Shihan; Zhang, Lingli; Deng, Dan; Luo, Wenlong (Frontiers in Neurology, 2024)
Background The association between benign paroxysmal positional vertigo (BPPV) and various mental disorders is still controversial. This study used the Mendelian randomization (MR) method to clarify the correlation between BPPV and seven mental disorders (bipolar disorder, depression, anxiety disorder, schizophrenia, suicidality, neuroticism, and mood swings) to aid in the exploration of BPPV complications and prevention and early treatment of mental disorders. Methods The datasets for BPPV and seven mental disorders were obtained from genome-wide association studies (GWASs). Two-sample MR was used to analyze the correlation between exposure (BPPV) and various outcomes (bipolar disorder, depression, anxiety disorder, schizophrenia, suicidality, neuroticism, and mood swings). A reverse MR study was also performed. The inverse variance weighting (IVW) method, the MR–Egger method, the simple mode method, the weighted mode method, and the weighted median method were selected. Results The MR analysis and the reverse MR analysis results did not reveal significant associations between BPPV and bipolar disorder, depression, anxiety disorder, schizophrenia, suicidal tendencies, neuroticism, and mood swings. Interestingly, neuroticism (IVW: OR = 1.142, 95% CI: 1.059–1.231, P = 0.001; P-MR-PRESSO adjustment = 0.0002) and mood swings (IVW: OR = 3.119, 95% CI: 1.652–5.884, P = 0.0004) may have a significant association with BPPV. After MR-PRESSO adjustment, there was no horizontal pleiotropy or heterogeneity, and a significant association between neuroticism, mood swings, and BPPV has still been suggested. Conclusion We conducted MR analysis on genetic data from European populations and discovered a causal relationship between BPPV and the seven mental disorders. Our research findings suggest that BPPV may not have a significant causal relationship with bipolar disorder, depression, anxiety disorder, schizophrenia, or suicidal tendencies. However, neuroticism and mood swings may be risk factors for BPPV.